2021
DOI: 10.1016/j.jbc.2021.101112
|View full text |Cite
|
Sign up to set email alerts
|

S-acylation of SARS-CoV-2 spike protein: Mechanistic dissection, in vitro reconstitution and role in viral infectivity

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 41 publications
4
48
0
Order By: Relevance
“…In light of the importance of S-acylation in SARS-CoV-2 infection, it is tempting to consider the possibility of developing selective inhibitors targeting ZDHHC acyltransferases involved in spike S-acylation ( Lan et al., 2021 ). Results described in this manuscript, together with in vitro reconstitution experiments described recently ( Puthenveetil et al., 2021 ), point to ZDHHC20 being one of the major players in S-acylation of spike. However, there are some discrepancies regarding which of the other specific ZDHHC family member or members could also be responsible for catalyzing this modification.…”
Section: Main Textsupporting
confidence: 61%
See 2 more Smart Citations
“…In light of the importance of S-acylation in SARS-CoV-2 infection, it is tempting to consider the possibility of developing selective inhibitors targeting ZDHHC acyltransferases involved in spike S-acylation ( Lan et al., 2021 ). Results described in this manuscript, together with in vitro reconstitution experiments described recently ( Puthenveetil et al., 2021 ), point to ZDHHC20 being one of the major players in S-acylation of spike. However, there are some discrepancies regarding which of the other specific ZDHHC family member or members could also be responsible for catalyzing this modification.…”
Section: Main Textsupporting
confidence: 61%
“…The coronavirus S2 subunit bears a cytoplasmic tail that is highly enriched in Cys residues (ten in the case of SARS-CoV-2). It has been shown that these Cys residues are sites for post-translational modification by S-acylation ( McBride and Machamer, 2010 ; Petit et al., 2007 ; Puthenveetil et al., 2021 ), a reaction that is mediated by host cell S-acyltransferases belonging to the zinc finger Asp-His-His-Cys domain-containing (ZDHHC) family of transmembrane enzymes. In humans there are around two dozen ZDHHC enzymes that mediate the S-acylation of thousands of proteins.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…During the preparation of this manuscript, Mesquita et al reported that ZDHHC5 knockdown in Hela cells or ZDHHC5 knockout in HAP-1 (human astrocyte precursor) cells had no significant effect on the palmitoylation of ectopically expressed S protein, but ZDHHC5 knockdown in Vero E6 (African green monkey kidney cells) significantly decreased S protein palmitoylation during SARS-CoV-2 infection [ 25 ]. Moreover, S protein palmitoylation was mainly mediated by ZDHHC8,9,20 via analyzing spike-incorporated radioactivity in Hela cells cotransfected with individual siRNAs targeting all human ZDHHCs [ 25 ], while Puthenveetil et al reported that ZDHHC2,3,6,11,20,21,24 were as putative palmitoylation enzymes for SARS-CoV-2 S protein modification by click-chemistry-based analyses of coexpression of S protein with individual ZDHHC [ 26 ]. Our results are consistent with the report of Mesquita et al However, in other reports, the interactions between SARS-CoV-2 S protein and ZDHHC5/GOLGA7 were confirmed by co-IP and the two host protein overexpressions in HEK293T cells enhanced S protein palmitoylation synergistically and ZDHHC5 knockdown decreased S protein palmitoylation and pseudovirus infection [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the identification of palmitoylated glycoproteins of Sindbis virus and Vesicular stomatitis virus in 1979 , many other palmitoylated proteins of viruses have been reported, such as hemagglutinin (HA) and proton channel M2 of influenza virus, glycoproteins of filoviruses and retrovirus (including HIV), fusion protein (F) of measles virus, the S-protein of coronavirus (CoV) (Veit, 2012;Kordyukova et al, 2019). It is noteworthy that the palmitoylation sites of SARS-CoV-2 spike protein have recently been identified and proved to be essential for SARS-CoV-2 fusion with the host cell (Mesquita et al, 2021;Puthenveetil et al, 2021). Palmitoylation modification of proteins may facilitate trafficking of glycoproteins on viral membranes, thereby promoting assembly and budding of progeny virions on infected epithelial cells (Veit et al, 2013;Demers et al, 2014).…”
Section: Palmitoylation Of Viral Proteinsmentioning
confidence: 99%